A Biophilic Design Guide to Environmentally Sustainable Design Studios - Wijesooriya, Niranjika; Brambilla, Arianna; Markauskaite, Lina. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book explores the current challenges of teaching biophilic design within environmentally sustainable design (ESD) education. It shows how design frameworks and success matrices can be used within ESD education, explores the development of biophilic design frameworks and shows how design thinking can be used to adopt biophilic design within ESD education. It introduces the new 'Process Bridging Technique (PBT)' that can be used to generate sustainable design frameworks able to fulfil the requirements of a performance-based approach and, at the same time, enhance human-nature connectedness. Based on an educational design research project developed in the past two years at the University of Sydney, this book informs new approaches to ESD education and bridges the spheres of research, education, and profession. It serves as a practical guide on how to systematically develop a design framework that can be used in architecture education, while presenting the pioneering 'Process Bridging Technique' developed by the authors.
1 Introduction -- 2 Developing design frameworks: Challenges, strategies and tools -- 3 An elemental view to perceive the built environment -- 4 Process Bridging Technique -- 5 Developing a Biophilic Design Framework -- 6 Biophilic design thinking.
Keywords: Technical education; Teaching; Educational technology; Professional education; Vocational education; Technology and Design education; Didactics and Teaching Methodology; Digital Education and Educational Technology; Professional and Vocational Education